In vitro evaluation of anti-inflammatory and antioxidant effects of Asparagus aphyllus L., Crataegus azarolus L., and Ephedra alata Decne.in monocultures and co-cultures of HepG2 and THP-1-derived macrophages - Kmail, Abdalsalam; Lyoussi, Badiaa; Zaid, Hilal; Imtara, Hamada; Saad, Bashar (Pharmacognosy Communications)
Introduction: Asparagus aphyllus L.,Crataegus azarolus L., and Ephedra alata Decne.have been used in traditional Greco-Arab herbal medicine to treat various metabolic and inflammatory diseases. However, to our knowl- edge, no scientific evidences regarding their anti-inflammatory effects have been published yet.This study aimedto evaluate the antioxidant and anti-inflammatory properties of Asparagus aphyllus L., Crataegus azarolus L., and Ephedra alata Decne.extracts using in vitro mono and co-culture systems. Methods: In the first phase of the current study we measured the total phenol, flavones and flavonol contents as well as the antioxidant activity using the DPPH scavenging assay, ABTS assay, and reducing power of the three plant extracts. In second phase, we used THP-1-derived macro- phages as a monoculture and co-culture with hepatic cell line (HepG2) to assess the effects of the three plant extracts on the production of LPS- induced pro-inflammatory (IL-6 and TNF - ) and anti-inflammatory (IL-10) cytokines.Results: All three extracts exhibit relatively high levels of phenolics, flavones and flavonols, which correlate with their antioxidant capacities. All three extracts were found to modulate the secretion levels of TNF - , IL-6 and IL-10 at non-toxic concentrations as measured with MTT and LDH assays. Conclusion: Taken together, our results suggest that the traditional uses of these extracts as anti-inflammatory remedies may be mediated by their significant antioxidant capacity, inhibition of pro-inflammatory cytokines secretion concomitant with enhancement of anti-inflammatory cytokines secretion.
Keywords: Anti-inflammatory; Antioxidant; Asparagus aphyllus L.; Crataegus azarolus L.; Ephedra alata Decne.